Oracle Fusion Middleware patterns : real-world composite applications using SOA, BPM, Enterprise 2.0, Business Intelligence, Identity Management, and Application Infrastructure /: real-world composite applications using SOA, BPM, Enterprise 2.0, Business Intelligence, Identity Management, and Application Infrastructure. (2010) - Unknown
No abstract available